Dr. Gerbrand Lindeque — Deep Plane Facelift — Cape Town - Lindeque, Gerbrand (DEEPPLANE™, 2026)
Surgeon profile record for Dr. Gerbrand Lindeque, practicing in Cape Town, South Africa. Tracked in the DEEPPLANE™ directory of listed deep plane facelift specialists. Published under CC-BY-4.0.
DPID-003266; accessed 2026-08-14; CC-BY-4.0
Keywords: deep plane facelift; facial plastic surgery; rhytidectomy; SMAS; south africa; cape town